The Influence Of Green Marketing On The Formation Of Green Brand Awareness Of Oriflame Brand In Jakarta City - Putri, Indriana Bella; Widodo, Arry (Owner : Riset dan Jurnal Akuntansi, 2024)
Oriflame uses a green marketing strategy to attract customers and keep them coming back for more.The manufacturing process for Oriflame's other product is known as the ringing process.The purpose of this article is to provide insight into Oriflame's efforts to promote green marketing and brand awareness.This article was written to find out how green marketing can increase Oriflame's brand awareness in Kota Jakarta.A deskriptif method was used in conjunction with a quantitative method that was used to collect responses from 100 Oriflame customers in Kota Jakarta Barat.Non-probability sampling and purposeful sampling are two types of sampling techniques.The SPSS 25 for Windows software was used to analyze the data in this study.The analysis of the deskriptif for the variable green marketing category was found to be superior by 88%, and the variable green brand awareness category was found to be superior by 87%.Green marketing has a positive and significant impact on green brand awareness, with a gain of 31,8 percent and a loss of 68,2 percent due to unidentified factors.